Anti-Double-Stranded DNA IgG Participates in Renal Fibrosis through Suppressing the Suppressor of Cytokine Signaling 1 Signals - Wang, Ping; Yang, Jie; Tong, Fang; Duan, Zhaoyang; Liu, Xingyin; Xia, Linlin; Li, Ke; Xia, Yumin (Frontiers in Immunology, 2017)
Suppressor of cytokine signaling 1 (SOCS1) participates in renal fibrosis by downregulating Janus kinase 2 (JAK2)/signal transducer and activator of transcription 1 (STAT1)-mediated cytokine signalling. Recently, it was found that anti-double stranded DNA (dsDNA) IgG induces the synthesis of profibrotic cytokines by renal cells. To explore the potential effect of anti-dsDNA IgG on SOCS1-mediated renal fibrosis, kidney tissues were collected from patients with lupus nephritis as well as MRL/lpr lupus-prone mice. The SOCS1 expression was evaluated in tissue samples. In addition, SCID mice were injected with anti-dsDNA IgG, followed by evaluation of SOCS1 levels. Renal resident cells were cultured in vitro, receiving the stimulation of anti-dsDNA IgG and then the measurement of SOCS1, JAK2, STAT1α, and profibrotic cytokines. Moreover, the binding of anti-dsDNA IgG to SOCS1-kinase inhibitory region (KIR) peptide was analyzed by surface plasmon resonance. We found that SOCS1 expression was inhibited, but JAK2/STAT1 activation was prominent in the kidney tissues of patients with lupus nephritis, MRL/lpr mice, or anti-dsDNA IgG-injected SCID mice. The cultured renal cells also showed SOCS1 downregulation, JAK2/STAT1 activation, and profibrotic cytokine promotion upon anti-dsDNA IgG stimulation. Surprisingly, anti-dsDNA IgG showed high affinity to KIR peptide, and competed with JAK2 loop for KIR. Additionally, a DNA-mimicking peptide (ALW) blocked the binding of anti-dsDNA IgG to KIR, and even partially abrogated the activation of JAK2/STAT1α signals and the expression of profibrotic cytokines in SCID mice. In conclusion, anti-dsDNA IgG downregulates SOCS1 expression, activates JAK2/STAT1 signals, and contributes to renal fibrosis; its peptide blockade may restore the SOCS1 inhibitory effect on the production of profibrotic cytokines, and finally ameliorate renal fibrosis in lupus nephritis.